2015
DOI: 10.1007/s10741-015-9481-z
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular assist devices: a kidney’s perspective

Abstract: The left ventricular assist device (LVAD) has become an established treatment option for patients with refractory heart failure. Many of these patients experience chronic kidney disease (CKD) due to chronic cardiorenal syndrome type II, which is often alleviated quickly following LVAD implantation. Nevertheless, reversibility of CKD remains difficult to predict. Interestingly, initial recovery of GFR appears to be transient, being followed by gradual but significant late decline. Nevertheless, GFR often remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 131 publications
2
27
0
3
Order By: Relevance
“…In fact, many LVAD patients experience renal dysfunction due to chronic cardiorenal syndrome [14]. This hemodynamic-renal disorder should often be normalized following LVAD implantation [15]. However, we hypothesize that there exists residual hemodynamic renal disease that may be related to the lack of pulsatility of the continuous-flow LVAD support that prevents long-term normalization of kidney functions.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, many LVAD patients experience renal dysfunction due to chronic cardiorenal syndrome [14]. This hemodynamic-renal disorder should often be normalized following LVAD implantation [15]. However, we hypothesize that there exists residual hemodynamic renal disease that may be related to the lack of pulsatility of the continuous-flow LVAD support that prevents long-term normalization of kidney functions.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have sought to identify risk factors for AKI development in the postoperative setting [3, 4, 7, 13-15]. Alba et al [13] found significant relations between postoperative AKI and cardiopulmonary bypass (CPB) time, reoperation following placement, and blood loss during the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Son iki dekaddır SDKY tedavisinde tüm dünyada etkin şekilde uygulanan SVDC implantasyon cerrahisi sonrasındaki hızlı metabolik ve fonksiyonel düzelmenin kalsiotropik hormonlar dolayısıyla KMY üzerine etkisi henüz tam olarak aydınlatılamamıştır. Ancak SVDC implantasyonu sonrası, kardiyak debinin arttığı, ameliyat öncesi dönemde gelişen hepatik ve renal fonksiyon bozukluğunun hızlı bir biçimde düzeldiği iyi bilinmektedir (10)(11)(12). Düzelen GFH, serum PTH üzerine etki ederek düşüşüne yol açmakta, bu da tip 1 kollajen amino terminal çapraz bağ telopeptidi (INTP, NTX) ve tip 1 kollajen karboksi terminal çapraz bağ telopeptidi (β-CTX) gibi kemik yıkım belirteçlerinde düşüşe, prokollajen-1 N-terminal peptid ve osteokalsin gibi yapım markerlarında ise istatistiksel anlamlı olarak artışa yol açmaktadır (4,10).…”
Section: Discussionunclassified
“…Son iki dekaddır SDKY tedavisinde kullanıma giren sol ventriküler destek cihazı (SVDC) implantasyonu ile hastaların fonksiyonel kapasitelerinin arttığı, hipoperfüzyona sekonder bozulmuş böbrek ve karaciğer fonksiyonlarının düzelttiği bilinmektedir (10). Hastaların ameliyat öncesi düşük olan 25-OH-D ve kalsiyum seviyelerinin, SVDC implantasyonu sonrası erken dönemde yükseldiği ve ameliyat öncesi yüksek seyreden parathormon (PTH) seviyelerinin ise ameliyat sonrası yine erken dönemde düştüğünü bildiren yayınlar bulunmaktadır (10)(11)(12). Herhangi bir medikal tedavi almadan, yalnızca vücut perfüzyonunu artıran SVDC implantasyonunun, hastaların diğer organ fonksiyonlarını düzelttiği gibi, osteoporozu tetikleyen parametreleri de iyi yönde etkilediği bildirilmiştir (10)(11)(12).…”
Section: Introductionunclassified
See 1 more Smart Citation